2014
DOI: 10.1248/bpb.b13-00488
|View full text |Cite
|
Sign up to set email alerts
|

Histological Protection by Nilvadipine against Neurotoxicity Induced by NOC12, a Nitric Oxide Donor, in the Rat Retina

Abstract: In the present study, we histologically examined the effects of nilvadipine on neuronal injury induced by intravitreal (i.v.) N-methyl-D-aspartate (NMDA) (200 nmol/eye) and intravitreal NOC12 (400 nmol/eye), a nitric oxide donor, in the rat retina. Morphometric evaluation at 7 d after injection of NMDA or NOC12 showed that treatment with nilvadipine (1 mg/kg, i.v.) 15 min prior to injection of NMDA or NOC12 dramatically reduced the retinal damage. These results suggest that nilvadipine protects neurons against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In the cataract model, the enhanced Ca 2+ in the lens promotes the aggregation of α-crystallin through the activation of calpain, and it has been reported that NIL, an anti-hypertensive lipophilic dihydropyridine-type calcium channel blocker, attenuates the enhanced intracellular Ca 2+ contents, resulting in alleviation of the calpain activation and α-crystallin aggregation [ 17 ]. Furthermore, Kuroki et al have also shown that treatment with NIL protected against toxicity through an anti-oxidative effect [ 37 ]. From these findings, we investigated whether combination with NIL-ONSs supports the anti-cataractogenic activity of LAN-ONSs.…”
Section: Discussionmentioning
confidence: 99%
“…In the cataract model, the enhanced Ca 2+ in the lens promotes the aggregation of α-crystallin through the activation of calpain, and it has been reported that NIL, an anti-hypertensive lipophilic dihydropyridine-type calcium channel blocker, attenuates the enhanced intracellular Ca 2+ contents, resulting in alleviation of the calpain activation and α-crystallin aggregation [ 17 ]. Furthermore, Kuroki et al have also shown that treatment with NIL protected against toxicity through an anti-oxidative effect [ 37 ]. From these findings, we investigated whether combination with NIL-ONSs supports the anti-cataractogenic activity of LAN-ONSs.…”
Section: Discussionmentioning
confidence: 99%